Revisiting OIC diplomacy and the Philippine government's policy response to the Moro struggle for self-determination - Campado, Prescillano D. (2011)
This paper analyzes in historical and policy perspectives the formation of the Moro National Liberation Front ?Organization of the Islamic Conference (MNLF-OIC) dyad, the ?whys? and ?wherefores? of the involvement of the OIC in the Southern Philippines problem, and the Philippine Government?s policy response to the Moro struggle for self-determination. The study straddles the terms of three Philippine presidents ? Ferdinand E. Marcos, Corazon C. Aquino, and Fidel V. Ramos. The methodology employed in this study is qualitative, using the historical-descriptive-cum-analytical approach. The triangulation method ? a mix of interview, content analysis, observation and experiential learning ? enriched and broadened the analytical spectrum in piecing together and interpreting otherwise disconnected data. This study presents the implications and consequences of the Philippine Government?s policy response to the Moro struggle for self-determination.
Includes bibliographical references (pages 190-198).